KESALAHAN SISWA SMA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN TEORI NEWMAN - Candraningsih, Yosy; Warmi, Attin (IKIP Siliwangi, 2023)
This research aims to describe student’s errors in solving math story problems with Newman’s Theory (Newman Error Analysis). This research is a qualitative descriptive reasearch. Subject of this research students of class X science 5. Data collection techniques are carried out by written tests and unstructured interviews. Data analysis techniques used in this research are data reduction, data presentation, and conclusions. Based on the results of the study, 1 student made a reading error, 1 student made a comprehension error, 6 students made a transformation error (mistake in changing the problem), 11 students made a process skill error, and 24 students made a encoding error (final answer writing error.